Analysis of Trusted Deposits at BPRS HIK Parahyangan KCP Indramayu: Advantages and Contributions to Empowering the Community's Economy - Didik Himmawan; Nisaul Isti’ani (Konsultan Jurnal Ilmiah Indonesia, 2025)
Fundraising is the main function of Islamic banks. BPRS Harta Insan Karimah (HIK) Parahyangan is an Islamic bank that follows sharia principles. One of the fundraising products at BPRS HIK Parahyangan is Sipanan Amanah. This trust deposit has several advantages, one of which is a light deposit, so that people with low incomes can use Amanah deposits. In addition, the role of BPRS HIK Parahyangan is not only as an institution that collects funds but also as a tool to encourage welfare and empower the economy of the people. The method used in this study uses a qualitative descriptive method by means of observation and interviews. The purpose of this study is to find out the advantages and contributions to the empowerment of the people in Amanah savings products at BPRS HIK Parahyangan KCP Indramayu. The results of this study explain the advantages of trust deposit products at BPRS HIK Parahyangan whose services are easy and safe. As well as contributing to the empowerment of the people.